The onchocerciasis hypothesis of nodding syndrome. - Robert Colebunders; Amber Hadermann; Joseph Nelson Siewe Fodjo (Public Library of Science (PLoS), 2023)
Nodding syndrome (NS) is a phenotypic presentation of onchocerciasis-associated epilepsy (OAE). OAE is an important public health problem in areas with high ongoing Onchocerca volvulus transmission. OAE, including NS, is preventable by strengthening onchocerciasis elimination programs. The presence of tau in OAE postmortem brains could be the consequence of neuroinflammation directly or indirectly induced by O. volvulus. Omics research is needed to investigate whether O. volvulus worms contain a neurotropic virus.